Strengths and Weaknesses of MSMEs in the Digital Era: Challenges and Opportunities for Transformation Towards Sustainable Competitiveness - Dwi Yanti Octaviani; Mila Kamelia Putri; Mashudi (Multicore International Journal of Multidisciplinary (MIJM), 2025)
This study aims to analyze the dynamics of Micro, Small, and Medium Enterprises (MSMEs) in responding to the rapid advancement of digital technology. The primary focus is to identify the internal strengths and weaknesses of MSMEs, as well as to evaluate external challenges and opportunities in the digitalization process to achieve long-term competitive advantage. Employing a qualitative approach through literature review and secondary data analysis, the study highlights operational flexibility and product innovation as key strengths of MSMEs. However, limitations in financial access, low levels of digital literacy, and infrastructure gaps remain significant barriers. Globalization and shifting consumer behavior further underscore the urgency for digital adaptation among MSMEs. On the other hand, digitalization presents significant opportunities such as market expansion, increased operational efficiency, and the enhancement of data-driven strategies. This article offers strategic recommendations, including improving digital literacy, gradual technological integration, and fostering collaboration within the digital ecosystem, to sustainably strengthen MSME competitiveness.